Hypercrosslinked polymers incorporated with imidazolium salts for enhancing CO2 capture. Issue 5 (21st January 2016) - Hu, Lingling; Ni, Huagang; Chen, Xiaolong; Wang, Lele; Wei, Ying; Jiang, Tengfei; Lü, Yaohong; Lu, Xiaolin; Ye, Peng
Abstract : Hypercrosslinked polymers (ILHCPs) incorporated with imidazolium salts were prepared using 4‐vinylbenzyl chloride, divinylbenzene, and imidazole ionic liquid monomers with various alkyl groups and anions by free radical copolymerization and Friedel‐Crafts alkylation reaction. The structures of ILHCPs were characterized by using FT‐IR, solid state 13 C CP/MAS NMR spectroscopy, TGA, and gas adsorption. ILHCPs exhibit excellent capability of CO2 adsorption compared with that of nonfunctional hypercrosslinked polymers (HCPs), although both the BET surface area (447–667 m 2 /g) and pore volume (0.24–0.28 cm 3 /g) of ILHCPs are less than HCPs. The synergistic effect from mirco/mesopore structures and imidazolium salts are proved to play a key role in enhancing the CO2 adsorption capability and selectivity over other gases for ILHCPs. It can be found that the imidazolium salts content in HCPs is more important compared with the pore texture for adsorbing CO2 . An optimal molar content of imidazolium salts groups is found to be 10.5% with the maximum CO2 uptake capability of 7.56 wt% and best CO2 adsorption selectivity (CO2 /N2 ) of 47.9/1 (273 K, 1 bar), while those of the HCPs are only 5.93 wt% and 27.9/1. Such results strongly suggest that ILHCPs can be promising applied in selective CO2 separation. POLYM. ENG. SCI., 56:573–582, 2016. © 2016 Society of Plastics Engineers